Childern’s color preferences and color choices for completing drawings of human figures in primary school - Pranckevičienė, Aistė; Žardeckaitė-Matulaitienė, Kristina; Soikinaitė, Indrė (Psichologija, 2009)
Drawing techniques are popular tools in children’s psychological assessment. It is supposed that colors in the child’s drawing could reflect the emotional state or feelings which he or she holds towards the topic being drawn. However, there is a lack of research to validate these interpretations.The aim of this work was to analyse pupils’ color preferences in I–IV grades and to investigate whet-her children systematically use specific colors in their drawings in response to emotional characterization of the figure. 1307 children (648 boys and 659 girls) from mainstream schools of Kaunas region, aged between 6 years 4 months and 12 years 3 months, participated in a color preference, mood rating and drawing session. All children rated the set of 11 pencils (from the most liked to the most disliked color) and completed three drawings of differently characterized human figures (neutral, nice, and nasty).The results of the study revealed gender differences in color preferences. Girls preferred bright colors (pink, yellow, sky blue, spring green, orange), while boys preferred darker tones of colors (blue, green, brown, black). All results are significant at p < 0.05. However, the most liked colors for both genders were bright (pink and sky blue), what is in line with color stereotypes used in children’s clothing and toys. The most disliked color for both genders was black; girls chose black as the most disliked color more often (p < 0.001).The results of the study indicate that children use specific colors when completing nice and nasty figures (p < 0.001). The strongest relationship was observed between a nice figure and the yellow color and a nasty figure and the black color. However, the choice of the color was related to a child’s color preference. The more preferred colors were used for completing of neutral and nice figures (p < 0.0001), while less preferred colors were used for nasty figures (p < 0.0001). Although the results of the study confirm the general association between characteristics of the topic being drawn and colors, the observed gender differences and the importance of color preference indicate that color interpretations during child’s psychological assessment should be done with caution. The implications for further research are discussed.
Keywords: none